Global Causes, Drivers, and Prevention Measures for Lost Fishing Gear - Richardson, Kelsey; Hardesty, Britta Denise; Vince, Joanna Zofia; Wilcox, Chris (Frontiers in Marine Science, 2021)
Abandoned, Lost or otherwise discarded fishing gear (ALDFG) comprises a significant part of global marine plastic pollution, with adverse consequences for fishers, the seafood industry, and marine wildlife and habitats. To effectively prevent and reduce ALDFG at source, an understanding of the major causes of and drivers behind fishing gear losses is required. We interviewed 451 fishers from seven countries around the world (Belize, Iceland, Indonesia, Morocco, New Zealand, Peru, and the United States of America) representing five key fishing gear types (gillnets, purse seine nets, trawl nets, longlines, and pots and traps) about why and under what circumstances they lose their gear. We also asked them their views on the most effective interventions to reduce gear losses. Across all major gear types and countries where interviews were undertaken, bad weather was the most common cause of gear loss, followed by interactions with wildlife (identified as a cause for loss by 81% and 65% of all fishers interviewed, respectively). Snagging gear on a bottom obstruction was a major cause of loss for gears that contact the seafloor, along with conflicts with other fishers, often via gear and vessel interactions, for gillnet and pot and trap fishers. Operational and behavioral characteristics such as gear type, trip length, and the party responsible to pay for gear repairs and replacements all significantly influenced gear losses. Gear maintenance was the most effective gear loss prevention measure across all gear types and countries reported by fishers, followed by training crew in gear management (identified as an effective prevention measure by 95% and 82% of all fishers interviewed, respectively). Actions available to fishers, managers and port operators to effectively prevent fishing gear losses include: gear maintenance; reducing active gear interactions with wildlife; reducing financial and administrative burdens for port reception facilities; reducing trip lengths; and targeting education and gear stewardship programs to fishers with limited ALDFG awareness, particularly those in low income fisheries and countries.